2017
DOI: 10.1038/s41531-017-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the neural correlates of corticobasal syndrome and corticobasal degeneration with systematic and quantitative ALE meta-analyses

Abstract: Corticobasal degeneration is a scarce neurodegenerative disease, which can only be confirmed by histopathological examination. Reported to be associated with various clinical syndromes, its classical clinical phenotype is corticobasal syndrome. Due to the rareness of corticobasal syndrome/corticobasal degeneration and low numbers of patients included in single studies, meta-analyses are particularly suited to disentangle features of the clinical syndrome and histopathology. Using PubMed, we identified 11 magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 41 publications
8
33
1
Order By: Relevance
“…Microstructural white matter changes were also observed in frontal and parietal cortices in the hemisphere contralateral to the clinically most affected body side of patients with CBS compared to healthy controls and patients with MCI. This is in line with previous studies showing significant asymmetric regional grey matter loss and white matter changes in motor cortex areas [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Microstructural white matter changes were also observed in frontal and parietal cortices in the hemisphere contralateral to the clinically most affected body side of patients with CBS compared to healthy controls and patients with MCI. This is in line with previous studies showing significant asymmetric regional grey matter loss and white matter changes in motor cortex areas [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another [ 18 F]AV1451 PET study has demonstrated increased tau binding in the putamen, globus pallidus, thalamus and precentral grey and white matter in the hemisphere contralateral to the clinically most affected side in six CBS patients [ 9 ]. Previous MRI studies have shown grey matter loss and white matter changes in precentral, superior frontal, and fusiform gyri, putamen and globus pallidus in CBS patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic and clinical data are presented in Table 1. CBS patients were used as clinical controls, as CBS is also neurodegenerative, but is associated with fewer neuropsychiatric and behavioral changes than FTD [14] and is predominantly characterized by atrophy in the posterior frontal lobes and basal ganglia [15,16], regions hypothesized to have fewer associations with sexual symptoms than anterior frontal and temporolimbic regions, as described above.…”
Section: Participantsmentioning
confidence: 99%
“…To restrict analyses to the hypothesized regions, ROIs were chosen based on established regions of atrophy in FTD (all phenotypes) [27][28][29][30][31] and CBS [15,16]. A mask of these regions was created using the Harvard Oxford Cortical and Subcortical atlases, available through the Functional MRI of the Brain Software Library [32] (Supplementary Material).…”
Section: Imagingmentioning
confidence: 99%
“…There have been no studies, to-date, exploring the neuropathological basis of sleep disturbances in CBS using neuroimaging techniques. A data-driven meta-analysis identifying and comparing the neural correlates of CBS for atrophy measurements included 200 CBS patients and 318 controls ( 187 ). This study identified four brain regions with significant atrophy: (1) the bilateral anterior thalamus; (2) the posterior midcingulate cortex, bilateral posterior frontomedian cortex and the premotor area/supplementary motor area; (3) the posterior superior frontal sulcus and precentral gyrus/middle frontal gyrus; (4) the left posterior superior frontal sulcus and middle frontal gyrus.…”
Section: Corticobasal Syndromementioning
confidence: 99%